The Relationship between Maxillofacial Injury Severity Score (MFISS) and Outcomes of Maxillofacial Trauma Patients at Dr. Mohammad Hoesin General Hospital (RSMH) Palembang, Indonesia - Valendra, Deo; Iqmal Perlianta; Erial Bahar (Sriwijaya Journal of Surgery, 2023)
Introduction: Maxillofacial trauma is an important public health problem, and understanding the relationship between injury severity and patient outcomes is critical for effective management. This study aimed to determine the relationship between the maxillofacial injury severity score (MFISS) and the outcomes of maxillofacial trauma patients at Dr. Mohammad Hoesin General Hospital, Palembang. Methods: An analytical observational study was conducted involving 121 maxillofacial trauma patients from April to May 2023. Data regarding patient characteristics, MFISS scores, type of management, length of stay, and mortality were collected and analyzed using statistical tests. Results: The majority of maxillofacial trauma patients were male (74.4%) and aged over 18 years (63.6%). Traffic accidents are the main cause of trauma (84.3%). The distribution of MFISS scores showed that 75% of patients had mild scores, 18.2% had moderate scores, and 5.8% had severe scores. Most patients underwent surgical management, with the majority having a length of stay of ≤7 days. The mortality rate was 2.5%. There was no significant relationship between the MFISS score and type of management (p > 0.05). However, there was a significant difference in the length of stay based on the MFISS score (p = 0.000). Patients with severe MFISS scores had significantly longer lengths of stay compared with patients with mild or moderate scores. In addition, there was a significant relationship between MFISS score and mortality (p = 0.000). Patients with severe MFISS scores had a higher risk of death compared with patients with mild to moderate scores. Conclusion: The MFISS score is associated with length of stay and mortality in maxillofacial trauma patients. However, there was no significant relationship between the MFISS score and the type of management.